Social Transformation and the Development of Islamic Civilization during the Reign of Utsman ibn Affan in Arabian Peninsula 644-656 Common Era - Qurratu Aini Aprilia; Muliasa Insani Candra; Tenry Hermawan (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2026)
Social transformation in Islamic history represents an important process marking the shift from a religious community to a complex political society. One of the most crucial phases of this transformation occurred during the reign of Caliph Utsman ibn Affan, characterized by territorial expansion and increasing social diversity within the Muslim community. This study focuses on political policies, administrative reforms, and social integration in Muslim society. It aims to analyze the contribution of Utsman leadership to political consolidation and social restructuring in the early Islamic period. This research is a study in Islamic political history employing the historical method, which consists of four stages: heuristics, source criticism, interpretation, and historiography. The results show that the reign of Utsman ibn Affan was a significant phase in the formation of early Islamic civilization. The codification of the Qur’an ensured textual uniformity across the expanding Islamic territories, while expansion into North Africa, Khurasan, and Asia Minor strengthened political authority and accelerated social integration among diverse ethnic groups. This process contributed to the development of a more organized social structure and Islamic civilization.